PENGARUH MODEL PEMBELAJARAN CARD SORT TERHADAP HASIL BELAJAR IPAS KELAS V SD NEGERI 107405 SEI ROTAN T.A 2024/2025. - Miftah Parinduri, Nurmayani, Irsan R; Robenhart Tamba, Khairul Usman (STKIP Subang, 2025)
This study aims to determine the influence of the Card Sort learning model on the IPAS (Integrated Natural and Social Sciences) learning outcomes of fifth-grade students at SDN 107405 Sei Rotan for the 2024/2025 academic year. The research employed a quantitative approach using a quasi-experimental design with a two- group pretest-posttest format. The sample consisted of two classes: Class V-A as the experimental group, which was taught using the Card Sort learning model, and Class V-B as the control group, which received direct instruction. Each class consisted of 33 students selected through purposive sampling. Data were collected through pretests and posttests using a validated essay-type test instrument, supported by observation and documentation techniques. Data analysis involved normality testing, homogeneity testing, and hypothesis testing using the independent sample t-test. The results indicated a significant difference in posttest scores between the experimental and control groups. The t-test analysis yielded a significance value of 0.001 (p < 0.05), suggesting that the use of the Card Sort learning model had a significant and positive effect on students' IPAS learning outcomes. Furthermore, students in the experimental class appeared to be more active, collaborative, and motivated throughout the learning process, which contributed to a deeper understanding of the subject matter. Therefore, the Card Sort learning model is considered effective in enhancing elementary school students’ learning outcomes in IPAS through active, critical-thinking, and cooperative learning.